Induction heating pyrolysis of landfilled plastic waste into valuable hydrocarbon fuels - Kaewpengkrow, Prangtip Rittichote; Phongsakul, Kittiphon; Chaiyaraksa, Chompoonut; Sricharoenchaikul, Viboon; Kachapongkun, Pongsakorn (International Journal of Renewable Energy Development, 2025)
This research investigated the pyrolysis process for plastic waste treatment using induction heating. The induction system involved a coil wrapped around insulated material to generate heat. The plastic waste was sourced from the Refuse-Derived Fuel (RDF) sorting process from a 15-year-old landfill in the province of Nonthaburi, Thailand. The pyrolysis was performed at temperatures ranging from 400 to 600°C with a batch reactor. The highest yield of pyrolysis oil was 27.6% wt. at 600°C. Energy consumption for converting plastic waste into oil ranged between 9.50 and 13.36 kWh, with the highest consumption at 600 °C. The produced pyrolysis oil at 600°C achieved the highest HHV of 41.33 MJ/kg. The GC/MS analysis of the pyrolysis oil revealed an increase in aromatic and hydrocarbons (C5-C11 and C12-C20) with rising temperature. These carbon fractions are suitable replacements for heavy oil or diesel fuel, as low-oxygenated compounds, and hydrocarbon content in pyrolysis oil are desirable. The amount of char produced at 400°C was the highest, with a yield that ranged from 45.2% wt. to 67.0% wt. Moreover, the pyrolysis process has a significant advantage in lowering greenhouse gas emissions (0.21–0.25% vol.), which releases less CO2 than the combustion of plastic waste. The findings therefore suggest that pyrolysis oil, which is produced under optimum conditions, can be used as a substitute liquid fuel in the industrial sector, and is consistent with the circular economy's concepts, promoting sustainability and utilizing resource efficiency.